A war of gifts : [compact disc, unabridged] : an Ender story - Card, Orson Scott (Card, Orson Scott. Ender's game., 2007)
The human race is a war with an alien race of insect-like beings. The first battles went badly, and now Earth prepares to defend itself against the imminent threat of total destruction at the hands of an inscrutable alien enemy. Earth builds a high-orbital facility called "Battle School" to train future military commanders from childhood. At the Battle School there is room for only one purpose--war. There is no room for cultural differences, religious observances, and certainly no room for Santa Claus. But when one student leaves a Sinterklaas Day gift in the shoe of his best friend, it sparks a war of the wills that the staff of the Battle School never bargained for.